FRI0145 A bayesian network meta-analysis on efficacy of biologics and small molecules in early rheumatoid arthritis. (12th June 2018) - Venerito, V.; Cacciapaglia, F.; Lapadula, G.; Iannone, F.
Abstract : Background: The use of several biologic drugs as well as small molecules, in combination or not with methotrexate (MTX), is licensed for the treatment of Rheumatoid Arthritis (RA). Treating patients within the 'therapeutic window of opportunity' may reset the disease's long-term trajectory. Which agent would fit better the need of promptly achieving remission of patients affected with early RA is currently a matter of debate. Ideally head to head comparison are required to estimate which treatment is the most effective. Alternatively, indirect comparisons based on a common comparator may be useful. Previous indirect comparisons 1 did not take into account all the biologics and small molecules approved for the treatment of RA, being also biassed, identifying early RA in patients with high variance of disease duration, ranging from to 6 months to 2 years. Objectives: To provide an estimate through a Bayesian Network Meta-Analysis of which biologic or small molecule in association with MTX is more likely to determine a good clinical response in patients affected with early RA (i.e. mean disease duration <1 year). Methods: A literature search was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) statement to identify results of Randomised Controlled Trials (RCTs) of biologic agents and small molecules at licensed doses to treat patients affected by early RA. MEDLINE, EMBASE, Cochrane Library, and Clinicaltrials.gov were searched for all published RCTs ranging from 1990 to September 2017. Patients had to fulfil the ACR 1988 revised criteria and/or the 2010 ACR/EULAR criteria for classified RA. We included all completed RCTs of biologics or small molecules in combination with MTX, compared with MTX plus placebo or in combination with other biologics or small molecules, in patients whose RA had mean duration of less than 1 year. American College of Rheumatology (ACR) 50% response and ACR 70% response had to be evaluated after one year of continuous treatment both in examined drug branch and in placebo branch. WinBUGS 1.4 software (MRC Biostatistics Unit, Cambridge, UK) was used to perform the analyses, using a a fixed-effect model. Results: Thirteen studies were included in the analysis. All the biologics as well as Tofacitinib proved to be more effective than MTX plus placebo in inducing an ACR50 response. In this regard, Tofacitib was the most effective overall (probability of being the best treatment: 75.04%) followed by Etanercept (21.52%). The agent with the highest probability of inducing ACR70 response was Etanercept (52.00%) followed by Abatacept (20.22%). All compared biologics in combination with MTX were superior to MTX alone in inducing ACR70 response. Conclusions: After one year of continuous treatment, Tofacitinib and Etanercept are the agents with the highest probability of inducing ACR50 response in patients affected by early RA, while Etanercept and Abatacept are the biologics with the highest probability of inducing ACR70. Reference: [1] Migliore A, et al. The Challenge of Treating Early-Stage Rheumatoid Arthritis: The Contribution of Mixed Treatment Comparison to Choosing Appropriate Biologic Agents. BioDrugs2016;30(2):105–115. Disclosure of Interest: None declared